The Role of the Investment Alert Task Force as a Form of Consumer Protection Against Fraudulent Investments - Pakpahan, Elvira Fitriyani; Hulu, Angellina Livonaria; Purba, Emmerita; Siregar, Jenni Yustina (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
This research delves into the function of the task force in bringing attention to questionable investments via consumer protection measures, particularly in cases when several individuals fall prey to fraud resulting from these questionable investments. The major foundation for integrating and improving law enforcement in the consumer protection sector is Law No. 8 of 1999 regulating consumer protection, which regulates consumer protection. The normative juridical approach, based on deductive inquiry that begins with the examination of legislative items, is the basis of this investigation. The foundational law for Indonesian investment rules is Law no. 25 of 2007, which addresses capital investment. The notion of "full disclosure" is one way that Law no. 8/1995 protects investors from potential harm. Other measures include harsh penalties for administrative infractions, criminal and civil litigation, illegal conduct, and defaults, as well as administrative penalties. Therefore, the government should be stricter in collecting public and consumer money for company licences, and the disadvantaged should take a more active role in selecting their financial investments to avoid falling victim to illicit ones.